Pengembangan perpustakaan politeknik: Digitalisasi, RFID, survei pemustaka, dan promosi - Arsyi Laurint (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2026)
Polytechnic libraries in Indonesia face multidimensional challenges in service development. However, these are often not addressed systematically due to limited resources and the absence of user-needs-based data to inform planning. This article documents and analyzes the Program Pengalaman Profesional Non-Kependidikan (P3NK) implemented at the Bandung State Polytechnic Library (Polban) for 30 working days from November 2025 to January 2026. This program was implemented in response to four identified operational problems: the lack of integration of all collections with the RFID system, the lack of digitization of old printed reports, the lack of empirical data on user needs, and the lack of a sustainable service promotion strategy. Using a qualitative descriptive approach that includes participant observation, online surveys, process documentation, and informal interviews, this program integrates six areas for development. Five of the six objectives were fully achieved: the survey resulted in a mapping of library users' needs based on 60 respondents as the first systematic empirical data, digitalization secured the scientific archive of published reports from 2006-2009 in a standardized PDF format, shelving ensured consistent collection order based on DDC, and Instagram promotion successfully introduced the Fiction Corner innovation to library users. RFID implementation was only partially achieved due to the program's limited duration. Four operational constraints were identified along with alternative solutions.